Effect of lactate group in the chiral chain of new compounds exhibiting short-pitch cholesteric or TGBA phase. Issue 8 (21st June 2018) - Novotná, Vladimíra; Fekete, Ladislav; Hamplová, Věra; Glogarová, Milada; Lejček, Lubor; Cigl, Martin; Pociecha, Damian
ABSTRACT: We have synthesised and studied lactic acid derivatives based on chlorine substituted molecular core, which is created from two biphenyls linked by an ester, and terminated with one or two lactic units in a chiral chain. The compounds with one lactate group exhibit cholesteric phase with rather short helix pitch (200 nm) in a broad temperature range. On contrary, compound with two lactate units reveals a stable TGBA phase, with transition temperatures substantially lower than those for one-lactate derivatives. We have studied mesophase behaviour and electro-optical properties, mostly based on the texture observation in polarising microscope. Additionally, we have used AFM and x-ray techniques to confirm mesophase identification and establish structural properties. GRAPHICAL ABSTRACT: